School Counselors' Use of Technology for Program Management. (January 2019) - Mason, Erin C. M.; Griffith, Catherine; Belser, Christopher T.
The use of technology in school counseling remains largely underinvestigated. In this descriptive study, researchers surveyed school counselors to examine ways in which they are using technology to manage their programs. Findings indicate that technology is underutilized by school counselors and is more likely to be used for program management tasks in the area of organization than for communication with and presentation of information to stakeholder groups. We discuss implications for practice, preparation and training, and future research.